Care and Value-Creating Education Put Into Action in Brazil: A Narrative Inquiry - Mokuria, Vicki; Wandix-White, Diana (Journal of Interdisciplinary Studies in Education, 2020)
This narrative inquiry highlights the experiences of self-identified Soka educators in a PreK-12th grade school in São Paulo, Brazil, as well as volunteers through a program called “Soka Education in Action.” Through their narratives, the role of care in value-creating education is explored as a critical aspect of education that supports students’ academic and personal growth and development, as well as educators’ professional identity and self-actualization. This study clarifies the essential qualities of Soka educators as understood and articulated by practitioners in the field. The narratives shared by study participants illuminate Soka education as a catalyst that fosters global citizenship by encouraging students to recognize their roles as agents of societal change and instruments of social justice.